Histologic grade as prognostic indicator for mucoepidermoid carcinoma: A population‐level analysis of 2400 patients. Issue 2 (14th June 2013) - Chen, Michelle M.; Roman, Sanziana A.; Sosa, Julie A.; Judson, Benjamin L.
<x xml:space="preserve">Abstract</x> Background Mucoepidermoid carcinoma (MEC) is an uncommon malignancy. To the best of our knowledge, this is the largest study investigating disease‐specific survival (DSS) of parotid MEC and the first population‐level study of the distribution of nodal metastases. Methods Patients with MEC of the parotid gland were identified in the Surveillance, Epidemiology, and End Results (SEER) database (1988–2009). Results We identified 2400 patients with MEC: 522 low grade, 1137 intermediate grade, and 741 high grade. Five‐year DSS rates for low‐grade, intermediate‐grade, and high‐grade MEC were 98.8%, 97.4%, and 67.0%, respectively (p < .001). Negative prognostic factors included high grade, increasing patient age, and tumor size, extraparenchymal extension, nodal metastases, and distant metastases. High‐grade MEC was more likely to have lymph node metastases in levels I to III (34.0%) than low‐grade (3.3%) and intermediate‐grade MEC (8.1%; p < .001). Conclusion Grade influences the prognosis and distribution of nodal metastases. Results indicate that management guidelines should vary based on grade. © 2013 Wiley Periodicals, Inc. Head Neck 36: 158–163, 2014